Evaluating the Public Administration Skills of Administrators at NIA-Kalinga Irrigation Management Office: Insights from Employees - Daluping, Salome; Sabado, Adriano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the public administration skills of administrators at the National Irrigation Administration-Kalinga Irrigation Management Office (NIA-KIMO), Tabuk City, as viewed by employees. It determined the respondents’ profile, assessed administrators’ skills in leadership, team management, digital skills, and organizational innovation, tested differences in employees’ viewpoints by profile, and examined relationships among the skill parameters. The study used a descriptive-correlational design with 122 NIA-KIMO employees selected through total population sampling. Data were gathered through a structured questionnaire patterned after public administration skills literature and treated using frequency counts, percentages, weighted mean, standard deviation, t-test, analysis of variance, and Pearson r correlation. Findings showed that most respondents were 31 to 40 years old, male, married, bachelor’s degree graduates, and had served for 6 to 10 years. Administrators’ public administration skills were rated High, with a grand mean of 4.09. Digital skills obtained the highest category mean, followed by organizational innovation, team management, and leadership. Age showed a significant difference in employees’ viewpoints, while sex, civil status, educational attainment, and length of service did not. The skill parameters were also significantly related, showing that strength in one public administration skill area is connected with strength in other areas. The study concludes that NIA-KIMO administrators demonstrate strong public administration competencies, particularly in digital work practices and organizational innovation, but continued capability-building remains necessary to sustain responsive, people-centered, and technology-enabled public service.